Gender specific regulation of tyrosine hydroxylase in Thy-1 knockout mice - Carkaci–Salli, N. (2012)
THYmocyte differentiation antigen 1 (Thy-1), is a cell surface glycoprotein found on T cells and neurons and is involved in cell-to-cell interactions. In addition, Thy-1 knockouts (KO) are a potential mouse model of restless legs syndrome (RLS) based on clinical observations and the role of dopamine in the disease. In this study, we analyzed the activity and quantity of tyrosine hydroxylase (TH; the rate-limiting enzyme in dopamine production) and determined phosphorylation levels for the enzyme (phospho-serine-40 (pSer-40)). There was no significant difference in the total TH activity and pSer-40 TH levels between Thy-1 KO and control groups; however, TH specific activity was significantly lower (by 26%) in Thy-1 KO mice. This difference is, in part, due to increased TH protein levels in this group (increased by 29%). When analyzed by gender, we determined that Thy-1 KO female mice striata contained less TH specific activity compared to control females (decreased by 41%) and male control or Thy-1 KO animals (decreased by 30%). TH specific activity and pSer-40 TH levels between male Thy-1 KO and control displayed no differences. However, pSer-40 TH was significantly higher in control females (38%) compared to control or Thy-1 KO males. The Thy-1 KO females exhibited significantly lower (28%) pSer-40 TH (normalized to GAPDH or TH) than control females. Indeed, the Thy-1 KO females had 50% of the pSer-40 TH found in controls. Our results suggest a gender effect on TH specific activity, TH protein levels and serine-40 phosphorylation of TH in Thy-1 KO female mice.